The Mammalian Protein–Protein Interaction Database and Its Viewing System That Is Linked to the Main FANTOM2 Viewer - Suzuki, Harukazu; Saito, Rintaro; Kanamori, Mutsumi; Kai, Chikatoshi; Schönbach, Christian; Nagashima, Takeshi; Hosaka, Junko; Hayashizaki, Yoshihide (Genome Research, 2003)
Here, we describe the development of a mammalian protein–protein interaction (PPI) database and of a PPI Viewer application to display protein interaction networks (http://fantom21.gsc.riken.go.jp/PPI/). In the database, we stored the mammalian PPIs identified through our PPI assays (internal PPIs), as well as those we extracted and processed (external PPIs) from publicly available data sources, the DIP and BIND databases and MEDLINE abstracts by using FACTS, a new functional inference and curation system. We integrated the internal and external PPIs into the PPI database, which is linked to the main FANTOM2 viewer. In addition, we incorporated into the PPI Viewer information regarding the luciferase reporter activity of internal PPIs and the data confidence of external PPIs; these data enable visualization and evaluation of the reliability of each interaction. Using the described system, we successfully identified several interactions of biological significance. Therefore, the PPI Viewer is a useful tool for exploring FANTOM2 clone-related protein interactions and their potential effects on signaling and cellular communication.